Interest: Factors for Increasing and Decreasing Memorization of The Qur`an - Kherul Mu'min; Imam Tabroni (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to find an increase in students' interest in memorizing the Qur`an at SMP IT Amsar. This study used a qualitative approach written descriptively, the methods used for data collection were observations, interviews and documentation. Data analysis and interpretation with Tringulation. The results of the research show that there has been an increase in graduates that occurred before, in 2021 there are 25 students memorizing 1 Juz, 3 students 2 Juz and 1 student 5 Juz. In 2022 it will increase to 1 juz with 36 students, 2 juz with 5 students and 5 juz with 5 students. Increased interest in memorizing the Qur`an due to changes in school principals and changes to the tahfidz al-Quran curriculum. The change in the tahfid curriculum which was previously a regular program became a tahkosus program. With the takhosus program, students can focus more on memorizing the Qur`an, so that students become more active in memorizing the Quran.